Management of Urogynaecological Problems in Pregnancy and Postpartum Period during Covid - Ayesha Basharat, Mugheera Hussain, Amna Najam, Uzma Saleem, Asma Mudassir, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Urogynaecological problems are the gynae related disorders of urinary system which affect women during pregnancy and postpartum period.Covid-19 also had an impact on these disorders. Objective: The main objective of this study is to find out how urogynaecological problems occur in pregnancy and postpartum period and how these problems were managed during covid 19. Study Design: Cross-sectional study Place and Duration: Gynaecology and Obstetrics department of Al-Nafees Medical College and Hospital, Islamabad, from 5th February 2020 to 6th August 2021. Method: We included 220 pregnant women in our study.Their age, body mass index, gestational age, mode of delivery, fetal age at the time of delivery were measured. Prevalence of urogynaecological problems in pregnant women was also noted. Among these 220 females, 50 females got infected with covid.We compared their complications with complications of pregnant women who weren’t infected with covid. Result: Body mass index of pregnant women with urogynaecological problems was 22 to 36 kg/m2. 12 to 14 kg weight increased during pregnancy.Gestational age at delivery was 38 to 42 weeks. Fetal weight was 2 to 4 kg at the time of birth. 62% women had vaginal mode of delivery while 38% had cesarian.Prevalence of urinary tract infections was 7% , stress urinary incontinence was 18 to 70%, uterine prolapse was 5 to 8% in pregnant women. 45% pregnant women had increased micturition frequency.Their were also some chances of formation of renal stones during pregnancy. Pregnant women who got infected with covid -19 had to face several other complications as well.These complications were managed with hygiene behaviour, balanced diet, exercise and medications. Conclusion: Urogynaecological problems are commonly found in pregnant women due to enlargement of kidneys and increased GFR during pregnancy. During pregnancy, uterus size increases which leads to compression of ureters and increased bacterial growth. Increased growth of bacteria causes urinary tract infections.Vaginal mode of delivery increases the risk of uterine prolapse.Covid-19 also had an impact on urogynaecological problems.These problems were managed during pandemic by avoiding direct contact. Keywords: Urogynecological problems, Pregnancy, Postpartum period, Covid-19